Incorporation of a Pd catalyst at the fuel electrode of a thin-film-based solid oxide cell by multi-layer deposition and its impact on low-temperature co-electrolysis - Thieu, Cam-Anh; Hong, Jongsup; Kim, Hyoungchul; Yoon, Kyung Joong; Lee, Jong-Ho; Kim, Byung-Kook; Son, Ji-Won (ROYAL SOC CHEMISTRY, 2017)
To enhance the electrochemical performance and syngas production in low-temperature co-electrolysis (LT-Co-EC), incorporation of Pd into the nickel-yttria-stabilized zirconia (Ni-YSZ) fuel electrode functional layer (FEFL) of a thin film-based solid oxide cell (TF-SOC) by multi-layer thin film deposition was investigated. The optimal configuration to insert a Pd layer without disturbing the surface and cross-sectional microstructure of the FEFL was fabricated by alternating multi-layer deposition of Pd by sputtering and nickel oxide-yttria-stabilized zirconia (NiO-YSZ) by pulsed laser deposition (PLD). TF-SOCs with Pd (Pd-cell) and without Pd (Ref-cell) were fabricated and compared based on the electrochemical reaction and syngas production in LT-Co-EC. The results showed that the catalytic activity by forming the Pd-Ni alloy on the electrochemical performance and thermochemical reaction are improved by Pd incorporation at low temperatures (<= 600 degrees C). Detailed microstructural analyses showed that Pd distributes from the electrode/electrolyte interface to a depth of several tens of microns in the anode support and forms a nano-structured Ni-Pd alloy, which contributes to improving the electrochemical reaction and thermochemical reactions such as water-gas-shift (WGS). It was also found that the performance stability was superior in the Pd-cell because pore array generation at the electrolyte/electrode interface was significantly suppressed in comparison with that of the Ref-cell.
Keywords: RENEWABLE ENERGY-SOURCES; NI BIMETALLIC CATALYSTS; SYNGAS PRODUCTION; STEAM/CO2 MIXTURES; CARBON-DIOXIDE; YSZ COMPOSITE; SOFC ANODES; PERFORMANCE; METHANE; MICROSTRUCTURE